Quiet eye predicts goaltender success in deflected ice hockey shots - Panchuk, D.; Vickers, J. N.; Hopkins, W. G. (European Journal of Sport Science, 2016)
In interceptive timing tasks, long quiet eye (QE) durations at the release point, along with early tracking on the object, allow performers to couple their actions to the kinematics of their opponent and regulate their movements based on emergent information from the object's trajectory. We used a mobile eye tracker to record the QE of eight university-level ice hockey goaltenders of an equivalent skill level as they responded to shots that deflected off a board placed to their left or right, resulting in a trajectory with low predictability. QE behaviour was assessed using logistic regression and magnitude-based inference. We found that when QE onset occurred later in the shot (950 ± 580 ms, mean?±?SD) there was an increase in the proportion of goals allowed (41% vs. 22%) compared to when QE onset occurred earlier. A shorter QE duration (1260 ± 630 ms) predicted a large increase in the proportion of goals scored (38% vs. 14%). More saves occurred when QE duration (2074 ± 47 ms) was longer. An earlier QE offset (2004 ± 66 ms) also resulted in a large increase in the number of goals allowed (37% vs. 11%) compared to a later offset (2132 ± 41 ms). Since an early, sustained QE duration contributed to a higher percentage of saves, it is important that coaches develop practice activities that challenge the goaltender's ability to fixate the puck early, as well as sustain a long QE fixation on the puck until after it is released from the stick.